(untitled) (Homoeopathy for All, 2025)
In recent years, the field of Homoeopathy in India has undergone significant transformation, primarily driven by the establishment of the National Commission for Homoeopathy (NCH) in 2020. This regulatory body, created under the National Commission for Homoeopathy Act 2020, has spearheaded a series of reforms aimed at enhancing the quality and integrity of Homoeopathy education and practice. These changes promise to elevate the standards of Homoeopathy, ensuring its practitioners are well-equipped to meet contemporary healthcare challenges. The NCH is founded with a vision, that is, to promote high quality and ethical practices in Homoeopathy and to ensure the safety and well-being of patients. By setting rigorous benchmarks for homoeopathic education and facilitating the development of competent professionals, the NCH envisaged effective contribution of Homoeopathy into the national healthcare system.